2015
DOI: 10.1515/hf-2015-0160
|View full text |Cite
|
Sign up to set email alerts
|

Hot water extraction of Norway spruce (Picea abies [Karst.]) bark: analyses of the influence of bark aging and process parameters on the extract composition

Abstract: The hot water (HW) extraction of Norway spruce (Picea abies [Karst.]) delivers condensed tannins and considerable amounts of other compounds. Yield and composition of the HW extracts were investigated as a function of natural weathering for up to 15 months. Total phenol monomers and oligomers were detected by Folin-Ciocaltau assay after fractionation by solid phase extraction (SPE). Procyanidins (PC) were determined by HPLC-UV after acid thiolysis and carbohydrates by HPLC combined with acid hydrolysis. Topoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 44 publications
(61 reference statements)
1
24
0
Order By: Relevance
“…The reasons for changes in bark chemical quality during the storage and weathering include enzymatic reactions (e.g., living cell respiration) and biological degradation (due to various bacteria and fungi), as well as thermo-chemical oxidative reactions at the presence of adequate oxygen and moisture [ 23 , 24 , 26 , 32 ]. Day-light-induced processes may also have taken place, leading to the formation of polymers and smaller oligomers but also degradation of structures, especially in the case of photosensitive stilbenes [ 9 , 17 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for changes in bark chemical quality during the storage and weathering include enzymatic reactions (e.g., living cell respiration) and biological degradation (due to various bacteria and fungi), as well as thermo-chemical oxidative reactions at the presence of adequate oxygen and moisture [ 23 , 24 , 26 , 32 ]. Day-light-induced processes may also have taken place, leading to the formation of polymers and smaller oligomers but also degradation of structures, especially in the case of photosensitive stilbenes [ 9 , 17 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, these extracts are obtained through the use of a hot pressurized sulfite aqueous solution [ 31 ]. Unfortunately, the amount of unextracted PACs can be as high as 62.5% in white grapes [ 32 ] and 62.3% in Norway spruce bark [ 33 ], resulting in a low yield process and a final extract that is mostly composed of PACs with lower degree of polymerization that are not as effective as the ones with higher degree of polymerization. Additionally, in order to achieve the intended mean degree of polymerization (mDP) further downstream processing is needed, making its final price prohibitive for most applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a significant volume of carbohydrates can increase the viscosity of tannin solutions, which decrease the penetration efficacy of the wood cells (Pizzi 2008, Thévenon et al 2009, Tondi et al 2013. Bianchi et al (2016) have proposed a way to increase the tannin concentration in softwood bark extracts relative to other compounds by inserting a cold-water extraction step before the hot water extractions. They found that phenolic monomers, mono-and oligosaccharides can be almost completely removed during the cold-water extraction.…”
Section: Introductionmentioning
confidence: 99%
“…bark using results from both laboratory and pilot-scale experiments and related previous research. It analyses two approaches to reducing the amount of co-extracts: (a) the introduction of a preliminary cold water step in the extraction process (Bianchi et al 2016); and (b) the use of membrane filtration for separation of the tannin from the non-tannin compounds (Nawas et al 2006). The information provided can help optimize the industrial production procedures and forecast their environmental performance.…”
Section: Introductionmentioning
confidence: 99%